2022
DOI: 10.3390/ijms23147642
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Identification of lncRNAs Regulating Sperm Motility in the Turkey (Meleagris gallopavo L.)

Abstract: Long non-coding RNAs (lncRNAs) are transcripts not translated into proteins with a length of more than 200 bp. LncRNAs are considered an important factor in the regulation of countless biological processes, mainly through the regulation of gene expression and interactions with proteins. However, the detailed mechanism of interaction as well as functions of lncRNAs are still unclear and therefore constitute a serious research challenge. In this study, for the first time, potential mechanisms of lncRNA regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 98 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…More recently, using public microarray data, Joshi et al identified fifteen functionally conserved lncRNAs across multiple studies in humans and mice 25 , which with HISTA, we explore deeply. Broadly, in the testis, lncRNA could A) regulate the expression of protein-coding genes involved in sperm production or function 26 . B) Directly interact with sperm cells or other cells in the testis 27 , potentially binding to receptors on the surface of sperm cells, altering their motility or ability to fertilize an egg or interact with the Sertoli cells or Leydig cells.…”
Section: Vignette 1: Novel Sets Of Lncrna Molecules Identified As Key...mentioning
confidence: 99%
“…More recently, using public microarray data, Joshi et al identified fifteen functionally conserved lncRNAs across multiple studies in humans and mice 25 , which with HISTA, we explore deeply. Broadly, in the testis, lncRNA could A) regulate the expression of protein-coding genes involved in sperm production or function 26 . B) Directly interact with sperm cells or other cells in the testis 27 , potentially binding to receptors on the surface of sperm cells, altering their motility or ability to fertilize an egg or interact with the Sertoli cells or Leydig cells.…”
Section: Vignette 1: Novel Sets Of Lncrna Molecules Identified As Key...mentioning
confidence: 99%